ANALISIS KINERJA SIMPANG KUMU PASIR PENGARAIAN PADA KONDISI EKSISTING DAN PADA TAHUN 2013 - Pada Lumba (Jurnal APTEK, 2012)
Transportation issues in Simpang Kumu is still public transports pick and drop passengers aroun the crossroad. This occurs both in the Muara Rumbai roads as well as on the Tuankau Tambusai road. This condition will certainly disrupt the smooth flow of traffic around the crossroad, especially related to the safety of road users. To overcome this problem needs to conducted an analysis of this crossroad, the crossroad capacity is still below the limit of tolerance is allowed or has passed the legal limit.The method used in this research is survey method, namely by placing the surveyors for each arm of the crossroad. Survey carried out at peak hours with an interval of time every five minutes. Task surveyors noted the number of vehicles entering the crossroad of the arms such as motorcycles, passenger cars and trucks on the paper survey forms. From the data obtained and analyzed primarily associated with the crossroad of performance such as capacity, delay and probability of the queue. Simpang Kumu performance analysis carried out on existing and forecast conditions in 2013.